Impact of vermicompost on residual and dissipation of chlorpyrifos in an entisol soil of semi-arid climate and variation in its fertility - Tito-Nova, Oscar; Choqueneira-Ccasa, Sara; Sarmiento-Sarmiento, Guido; Lipa-Mamani, Luis (REVISTA TERRA LATINOAMERICANA, 2024)
Excessive use of chlorpyrifos af fects the quality of agricultural soils causing negative ef fects on the safety of harvested food. The behavior of chlorpyrifos residues depends on soil properties, especially organic matter. Our aim in this research was to determine the ef fect of the application of vermicompost on the residual and dissipation of chlorpyrifos in an entisol soil of semi-arid climate with variations in its edaphic fertility. Four treatments were studied. T1: 7.5% vermicompost (V) and 92.5% soil (S); T2: 5% V and 95% S; T3: 2.5% V and 97.5% S; T4: 0% V and 100% S. The treatments were subjected to a seven-day incubation period. Subsequently, a dose of chlorpyrifos of 1.5 mg kg-1 as active ingredient was applied once for each treatment. A completely randomized design was used with three replicates for each treatment, forming 12 experimental units. The analytical determination of chlorpyrifos was carried out by high performance liquid chromatography (HPLC). The evaluations were carried out 1.7, 14, 28, 42, 70 and 98 days af ter the application of chlorpyrifos. The results showed that the incorporation of vermicompost to the soil at increasing levels promoted a decrease in the residual concentration of chlorpyrifos and facilitated its gradual dissipation. The chlorpyrifos dissipation curves correspond to a first order logarithmic equation where the ef fects of the treatments caused greater dissipation of chlorpyrifos as the evaluation period elapsed. At 98 days of evaluation, T1 registered lower residuality (0.786 m kg-1), higher daily dissipation rate (0.008) and lower half-life of chlorpyrifos (86.64 days). At the end of the research period, edaphic levels of P, K, EC and CEC increased while OM, N and pH decreased af ter vermicompost application.